A proposed organized in-service training programme for primary teacher educators in Ceylon based on in-service education practices in some Asian countries - Jayasekera, Jayasena 1916- (s.n.], 1967)
The study gathered information to support the development of a proposal for the establishment of an Institute for in-service training practices in the Asian centres in the view of discovering probable implications for Ceylon.